Silibinin induces in vitro M2-like phenotype polarization in monocytes from preeclamptic women - Gomes, Virgínia Juliani [UNESP]; Nunes, Priscila Rezeck [UNESP]; Matias, Mariana Letícia [UNESP]; Ribeiro, Vanessa Rocha [UNESP]; Devides, Amanda Carreira [UNESP]; Bannwart-Castro, Camila Ferreira [UNESP]; Romagnoli, Graziela Gorete [UNESP]; Peraçoli, José Carlos [UNESP]; Peraçoli, Maria Terezinha Serrão [UNESP]; Romao-Veiga, Mariana [UNESP] (Elsevier, 2020)
Preeclampsia (PE) is a pregnancy-specific syndrome featuring intense activation of circulating monocytes and an imbalance between pro- and anti-inflammatory cytokines. The present study evaluated the immunomodulatory effect of silibinin (Sb) on the expression of surface markers and the nuclear transcription factor NF-κB signalling pathway of monocytes from preeclamptic women. Monocytes were cultured with or without Sb, and the mean fluorescence intensity of the surface molecules TLR4, CD64, and CD163 as well as the intracellular transcription factors IκB-α and NF-κBp65 was analysed by flow cytometry. The concentration of cytokines in the monocyte culture supernatant was determined by cytometric bead array and ELISA immunoassay. The results showed that the in vitro treatment of monocytes from preeclamptic women with Sb downregulated the endogenous activation of NF-κB and the expression of surface receptors TLR4 and CD64, and reduced the synthesis of the pro-inflammatory cytokines interleukin 1 (IL-1β), IL-6, IL-8, IL-12p70, IL-23, and tumour necrosis factor alpha (TNF-α) compared with cultures not treated with Sb. The presence of this flavonoid in monocyte cultures increased the expression of CD163 and IκBα and the release of IL-10 and transforming growth factor beta (TGF-β) in the culture supernatants, polarising these cells from the M1-like profile to the M2-like profile. The anti-inflammatory activity of Sb on the NF-κB activation pathway and induction of cell polarisation to the M2 profile was confirmed by an in vitro assay using monocytes from healthy, non-pregnant women. Treatment of monocytes from preeclamptic women with Sb polarises the cells to the M2-like phenotype, suggesting that this flavonoid has an immunomodulatory effect on the sterile inflammation characteristic of PE.
Keywords: Cytokines; Monocyte subpopulations; NF-κB pathway; Preeclampsia; Silibinin